2020
DOI: 10.23917/jk.v12i2.9763
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Intake, Vitamin C, Purine Intake, Body Mass Index and Uric Acid Levels in Man (Aged 26-45 Years Old) in Rw 05 Sub-District Bukit Duri Jakarta

Abstract: Hyperurisemia is a condition that uric acid levels in blood above the normal value. Uric acid levels are influenced by consumption of purines, carbohydrate intake, protein, fat, vitamin C and Body Mass Indeks (BMI). The purpose of study was to describe correlation of consumption of purine, carbohydrate intake, protein, fat, vitamin C, BMI and uric acid level in man (aged 26-45 years old) in RW 05 sub-district Bukit Duri Jakarta, 2017. This study was used a cross sectional design with sample of 56 man aged 26-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Previous study stated that there was significant relationship between protein intake and uric acid levels (p=0,001), also fat intake and uric acid levels (p=0,001). On the other hand, this study was similar to other study that mentioned there was no significant relationship between carbohydrate intake and uric acid levels (p=0,259) (Wahyuni et al 2019). Almost 50% subjects had high carbohydrate intake, and the carbohydrate intake ranged from 232 grams to 448 grams.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Previous study stated that there was significant relationship between protein intake and uric acid levels (p=0,001), also fat intake and uric acid levels (p=0,001). On the other hand, this study was similar to other study that mentioned there was no significant relationship between carbohydrate intake and uric acid levels (p=0,259) (Wahyuni et al 2019). Almost 50% subjects had high carbohydrate intake, and the carbohydrate intake ranged from 232 grams to 448 grams.…”
Section: Resultssupporting
confidence: 89%
“…Previous study showed that there was correlation between fat intake and uric acid levels because the excretion of acid can be inhibited by fat. Higher fat intake can increase uric acid levels (Wahyuni et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…9,10 However, a recent study in various provinces in Indonesia showed the prevalence of hyperuricemia remained high, approximately 18.6%; 36.36%; 37.5%; 47.6%. 8,[11][12][13] Uncontrolled hyperuricemia causes acute arthritis attacks and manifests to chronic gout conditions, resulting in decreased kidney function and decreased quality of life. 14 The older adults are a group that was prone to experiencing gout.…”
Section: Introductionmentioning
confidence: 99%